Preparing EFL pre service teachers for inclusive teaching: The students' perception on the outcome-based evaluation of the introduction to inclusive education course - Kirana, Novera Putri; Lintangsari, Alies Poetri; Emaliana, Ive (English Language Teaching Educational Journal, 2024)
Inclusive Education has been an emerging initiative in Indonesia, yet, the implementation of it in English Language Teaching is less explored. English Language Education Department, Faculty of Cultural Studies, Universitas Brawijaya has initiated a course called Introduction to Inclusive Education to prepare students with inclusive teaching competencies. This course has been implemented for 2 years, a course evaluation needs to be carried out to evaluate and improve the course quality. This present study reports the evaluation of the aforementioned course with the Framework of Outcome Based Education from the students’ perspective. Inviting 129 students enrolled in the course, this research revealed that most of students agreed that this course has met their expectation toward the offered competencies (M=3,25), positive perception toward course activities (M=3,12), positive perception toward the benefits of course materials (M=3,19), and positive perception toward tutor performance (M=3.2). Surprisingly, despite the students' agreement on the usefulness of the courses, they also acknowledged that the course materials are pretty difficult (M=3,15). The result of this course evaluation shed a light on the importance of adjusting the materials to be more achievable by the students so they have confidence in implementing inclusive teaching practices.